Case Report: A Case of Renal Cell Carcinoma Unclassified With Medullary Phenotype Exhibiting a Favorable Response to Combined Immune Checkpoint Blockade - Takeda, Masashi; Kashima, Soki; Fuchigami, Yasushi; Yoshino, Takayuki; Kataoka, Tatsuki R.; Yamasaki, Toshinari; Kagamu, Hiroshi; Kobayashi, Takashi; Akamatsu, Shusuke (Frontiers in Immunology, 2022)
Renal cell carcinoma unclassified with medullary phenotype (RCCU-MP) is an extremely rare variant of kidney cancer with poor prognosis. Recently, immune checkpoint inhibitors (ICIs) have been the mainstay of treatment for advanced clear cell renal cell carcinoma (RCC). However, the efficacy of ICI in the treatment of RCCU-MP remains unclear. Here, we report about a 63-year-old Japanese man who was referred to our hospital with a diagnosis of RCC of the left kidney with multiple lymph node involvement (cT3aN1M1). The patient underwent nephrectomy with lymph node biopsy, which was histopathologically diagnosed as RCCU-MP. Thereafter, he received combined immune checkpoint blockade with nivolumab and ipilimumab. After induction therapy, follow-up computed tomography revealed shrinkage of the metastatic lymph nodes. Moreover, the patient was relieved of his subjective symptoms and his performance status improved. However, after 15 months, maintenance ICI therapy was discontinued because of disease progression, and the patient died 28 months after diagnosis. Longitudinal analysis of peripheral blood mononuclear cells revealed increased stem cell memory and central memory CD8+ T-cell subsets during response to therapy, and enhanced expression of exhaustion markers on CD8+ T cells upon treatment resistance. Combined immune checkpoint blockade could be effective in the treatment of metastatic RCCU-MP.